Enhanced Mechanical Properties of Polyvinyl Chloride-Based Wood–Plastic Composites With Pretreated Corn Stalk - Shen, Tao; Li, Minghui; Zhang, Bo; Zhong, Lingxia; Lin, Xiran; Yang, Pengpeng; Li, Ming; Zhuang, Wei; Zhu, Chenjie; Ying, Hanjie (Frontiers in Bioengineering and Biotechnology, 2022)
Wood plastic composites (WPCs) is a type of environmentally friendly materials widely used in daily life. This paper selected a low-value biomass, corn stalk (CS), as the lignocellulosic resource for PVC-based WPCs. To depict the relationship between lignocellulosic composition (cellulose, hemicellulose and lignin) and mechanical performance of WPCs, pretreatments have been optimized to selective removal of lignin using an alkaline-EtOH stewing process and selective removal of hemicellulose using an acid stewing process. The αC sample, in which both lignin and hemicellulose were removed, shows the highest degree of crystallinity (72.60%) as estimated from XRD results, and fibrous morphology with the highest aspect ratio as seen in SEM images. Compared to PVC/CS, PVC/αC gives a substantial increase in tensile strength and modulus by 37.21% and 21.66%, and in flexural strength and modulus by 29.98% and 34.88%, respectively. These improvements lie in the reinforcing effect of fibrous structure and the improved interfacial compatibility as prove by SEM and DMA results. Considering the extracted lignin and hemicellulose can be further developed to valuable bio-chemicals, the pretreatment to CS adds value into both WPC materials and bio-refinery products.